The Role of Trade Unions as a Subject of Social Partnership in the Settlement of Labor Disputes - RAKHIMOVA, Asem M.; KAISHATAEVA, Asel K. (Journal of Advanced Research in Law and Economics, 2020)
The most important actor of the system of social partnership are trade unions, which often act as democratic institutions of society. The aim of the study is to determine the role of trade unions as a participant in social partnership in the system of settlement of labor disputes in Kazakhstan, using the experience of foreign countries as an example, creating a mechanism for social protection of workers in the form of a balanced system of state and market regulators and strengthening the role of trade unions in the occupational safety management system. The following methods were used as methods of scientific research: analysis of literary sources, the study of regulatory legal acts, special legal, comparative legal. The author focuses on the problems faced by employees in resolving labor disputes. The labor legislation of Kazakhstan regulates the procedure for issuing acts of an employer, preparing a draft collective agreement, the procedure for resolving labor disputes, etc. All this should be conducted taking into account the opinion or in agreement with the representatives of employers, but today, as practice shows, all these procedures take place without proper coordination, especially in commercial enterprises with a non-state form of ownership. According to the author, the regulation of labor disputes is just the direction where there is close interaction between trade unions and the state is a clear manifestation of social partnership.